Optimal Proportion of Similar Materials and Rockburst Tendency of White Sandstone - Chaoyi Ma; Zhengguo Zhu; Zhichun Fang; Zhaobin Li; Liu Liu (Advances in Materials Science and Engineering)
To explore the tendency of rockburst, a similar material ratio was optimised based on white sandstone. Quartz sand, iron powder, gypsum, cement, retarder, and a water-reducing agent were used as the main materials. The orthogonal test design principle was used to determine the four-factor and four-level orthogonal test design with the quartz sand content, iron powder content, gypsum-cement ratio, and sand particle size as the influencing factors. Uniaxial compression tests and tensile tests were conducted on similar material models. The tensile strength and elastic modulus were analysed, the significance of each influencing factor was investigated, and the test results of the similar materials were fitted. The optimal ratios of the similar materials of white sandstone were found to be quartz sand content of 36%, iron powder content of 1.9%, gypsum-cement ratio of 1.8 : 1, and sand particle size of 2–4 mm. The physical and mechanical properties of the similar materials were consistent with those of white sandstone. The mechanical properties of the similar materials were compared with those of the original rock. By judging the rockburst propensity and verifying the index, it is concluded that the similar materials can effectively simulate the characteristics of white sandstone, which is an ideal similar material of rockburst, and they all show strong rockburst propensity. The rock specimens with optimal proportions were produced, and the internal energy changes and rockburst mechanisms of the model at different temperatures were discussed. The results show that the rockburst process is closely related to energy, such as thermal energy and elastic strain energy, and the rock failure process can be divided into three main stages: energy accumulation, microcrack formation and propagation, and crack penetration and bursting. It provides an experimental basis for the preparation of rockburst similar materials that are more in line with the actual situation of the project and provides a basis for discussing the energy criterion of rockburst.